Comparison of Risk Factors Use Personal Protection Equipment and Exposure to Sulphate Content with Irritant Contact Dermatitis in Car Washing Officers in Malang City - Pravitasari, Dwi Nurwulan; Nerdenaesti, Aliyyudestrina Windya; Danurwendra, Syahdan Millenia; Illahika, Anung Putri (UNUSA Press, 2023)
Background: Irritant contact dermatitis (ICD) is an occupational disease that involves non-immunological inflammatory mechanisms of the skin, resulting from a response to exposure to irritants, physical, or biological. ICD disease often occurs in car wash employees who are exposed to laundry soap containing sulfate. Most of the factors that cause ICD are the length of exposure to chemicals or from the workers themselves such as knowledge, use of personal protective equipment, and personal hygiene. The purpose of this study was to determine the effect of using personal protective equipment (PPE) and exposure to sulfate content of car wash soap on the incidence of ICD in car wash employees in the city of Malang with and without a history of skin disease. Method: The research method uses an analytic observational research type with a cross sectional design. The samples studied were 84 respondents who were car wash employees in the city of Malang, both those who had a history of skin diseases (39 respondents) and those who did not have a history of skin diseases (45 respondents). Data were analyzed using univariate and bivariate tests with SPSS application. Results: The results of the chi square test showed that there were significant differences in risk factors (p < 0.05) on the incidence of ICD. Conclusion: The conclusion of this study is there is an effect of the use of PPE and exposure to sulfate content on the incidence of ICD in car wash employees in the city of Malang with and without a history of skin diseases.